(3ehShYI GdJGQjN GdESdGej h GdMVGQI GdESdGejI (B:s (3GdOhdI GdCehjI h GdMQcGJ GdacQjI h GdKhQjI aj YgOgG (B/s - (3TdHj,CMeO s ((3GdbGgQI (B:s (3ecJHI GdfgVI GdeUQjI ,s, 1973)
(3OQGSI JMdjdjI TGedI dJGQjN GdYGde GdESdGej cdg ef eWdY GdESdGe MJi GdCf eY OQGSI GdLhGfH GdMVGQjI GdJj CSge HgG GdeSdehf aj JQbjI GdYeQGf h JWhjQ GdLfS GdHTQjs
Keywords: (3GdJGQjN GdESdGej s; (3GdMVGQI GdESdGejIs; (3ehShYIs